Human well-being outcomes of large-scale marine protected areas - Baker, Dana; Bennett, Nathan J.; Ban, Natalie C. (Marine policy, 2025)
Large-scale marine protected areas (LSMPAs, >100,000 km2) account for over half of the global ocean under protection, yet little is known about their outcomes for people. We conducted a review of the peer-reviewed literature to identify studies that investigated human well-being outcomes from forty-four (44) LSMPAs worldwide. Sixty-four (64) peer-reviewed articles were identified, which analyzed well-being outcomes in 18 of the 44 LSMPAs. For LSMPAs where human well-being outcomes have been studied, outcomes were highly variable and LSMPAs with more than three studies had both positive and negative outcomes. Fifty-two (52) percent of human well-being outcomes reported were positive, while 42 percent were negative, and 6 percent showed no change. Results highlight diverse domains of human well-being as the subject of studies, indicating that as increasing attention is placed on human well-being and MPAs, more aspects of social outcomes are being investigated. However, the scientific literature also left important variables of human well-being understudied, including the differentiated outcomes that LSMPAs can impart on race, gender, social class, and diverse cultural groups. Our review is a first step towards synthesizing existing knowledge but highlighted that our understanding is nascent. Future studies are needed that focus on understanding the differentiated impacts of LSMPAs across different social groups and that examine the processes that lead to different human well-being outcomes. With global commitments to protect 30 % of the oceans driving ongoing interest in LSMPA establishment, it is crucial to gain a better empirical understanding of the effect of LSMPAs on human well-being.